2008
DOI: 10.1038/nchembio.113
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative exploration of the catalytic landscape separating divergent plant sesquiterpene synthases

Abstract: Throughout molecular evolution, organisms create assorted chemicals in response to varying ecological niches. Catalytic landscapes underlie metabolic evolution, wherein mutational steps alter the biosynthetic properties of enzymes. We report the first systematic quantitative characterization of a catalytic landscape underlying the evolution of sesquiterpene chemical diversity. Based on our previous discovery of a set of 9 naturally occurring amino acid substitutions that functionally inter-converted orthologou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
191
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(196 citation statements)
references
References 34 publications
5
191
0
Order By: Relevance
“…A growing body of evidence suggests that many enzymes exhibit broad catalytic specificity and/or promiscuity 11,17 , particularly enzymes in secondary metabolism [44][45][46][47][48] . Broad specificity may therefore relate to the recent divergence of secondary and specialized metabolism enzymes relative to primary metabolic enzymes, as well as the intensity of selection being weaker than it is for enzymes in primary metabolism 45,49 .…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that many enzymes exhibit broad catalytic specificity and/or promiscuity 11,17 , particularly enzymes in secondary metabolism [44][45][46][47][48] . Broad specificity may therefore relate to the recent divergence of secondary and specialized metabolism enzymes relative to primary metabolic enzymes, as well as the intensity of selection being weaker than it is for enzymes in primary metabolism 45,49 .…”
Section: Discussionmentioning
confidence: 99%
“…However, owing to descent with modification and its historical record encoded in genomes, recent technological advances have facilitated the generation of large-scale ancestral mutant libraries based on phylogenies of extant enzyme sequences (Weinreich et al 2006;O'Maille et al 2008;Goldsmith and Tawfik 2012). These developments make it possible to peer into the past with an admittedly slightly out of focus "telescope."…”
Section: Future Perspectivesmentioning
confidence: 99%
“…TPSs and type III PKSs often produce one major product together with a number of minor products. Moreover, the product distribution profiles of these enzymes are often conditionally sensitive and are exquisitely attuned to minor mutational changes within and around the active site (Austin et al 2004;O'Maille et al 2008). Although TPSs and PKSs belong to disparate protein folds, they converge to exploit similar catalytic principles to direct cyclization of their respective highly reactive intermediates.…”
Section: The Role Of Catalytic Promiscuity In Enzyme Evolvabilitymentioning
confidence: 99%
“…By systematically exploring the relationship between sequence and function, Yoshikuni et al (2006) identified and mutated a set of hot spots near the active site of sesquiterpene synthases that results in biocatalysts selectively catalyzing the formation of a spectrum of sesquiterpene products). Furthermore, O'Maille et al (2008) systematically investigated the relationship between a combination of nine naturally occurring amino acid substitutions and the resulting sesquiterpene product spectra. However, the application of the resulting catalysts was not attempted in planta for diversifying plant metabolism.…”
Section: Online)mentioning
confidence: 99%